Current understanding of rheumatoid arthritis therapy in pregnancy - Swain, Sujata; Jena, Paresh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Pregnancy in most cases is associated with remission of rheumatoid arthritis (RA), but a quarter of patients continue to have active disease or even worsening of the disease and most patients who improve, relapse in the postpartum period. Patients with RA do not have decreased fertility. A majority of patients with RA may go in remission, but patients who continue with the disease activity require treatment. Drugs that may be safely used during pregnancy include NSAIDs except in third trimester, corticosteroids as low dose prednisone. The preferred disease-modifying agents (DMARDs), during pregnancy are sulfasalazine and hydroxychloroquine. Azathioprine and cyclosporine can be used if the benefits outweigh the risks. Methotrexate and lefunomide are contraindicated and must be prophylactically withdrawn before a planned pregnancy. Biologics like anti-TNF agents, rituximab and abatacept generally should be stopped when pregnancy is discovered. An overall rational approach is highly warranted to treat RA during pregnancy.